Rethinking Mass Media as The Fourth Pillar of Democracy in Indonesia - Karman, Karman; Mudjiyanto, Bambang (Jurnal Hukum Replik, 2024)
Indonesia, as a democratic nation, traditionally relies on its executive, legislative, and judicial institutions, along with the mass media, which has often been regarded as the fourth pillar of democracy. However, this research challenges the perception of mass media as an independent pillar. By analyzing Indonesia's shifting media landscape, drawing from a wide range of sources—including academic studies and examinations of media mogul influence in politics—this study identifies a significant change in the relationship between mass media and democratic governance. Our findings suggest that mass media has become entangled with political oligarchies, leading to a homogenization of news content and a prioritization of political agendas over democratic principles. In contrast, we observe that new media platforms, such as Twitter and various websites, have emerged as spaces for public political activism, particularly evident during key democratic events like the 2019 presidential election. Therefore, we advocate for a more comprehensive understanding of media's role, encompassing not just traditional mass media but the entire media ecosystem that sustains democratic governance.Keywords: Media Landscape, Media’s Role, Political Activism, Societal Values